The determination of waste generation and composition as an essential tool to improve the waste management plan of a university. (July 2016) - Gallardo, A.; Edo-Alcón, N.; Carlos, M.; Renau, M.
Highlights: We present a methodology to study waste generation and composition at a universities. It shows statistical tools to establish the variation of waste over one school year. It estimates the waste generation and composition of a Spanish University. It will be useful to improve waste management in a company or institution. Abstract: When many people work in organized institutions or enterprises, those institutions or enterprises become big meeting places that also have energy, water and resources necessities. One of these necessities is the correct management of the waste that is daily produced by these communities. Universities are a good example of institution where every day a great amount of people go to work or to study. But independently of their task, they use the different services at the University such as cafeterias, canteens, and photocopy and as a result of their activity a cleaning service is also needed. All these activities generate an environmental impact. Nowadays, many Universities have accepted the challenge to minimize this impact applying several measures. One of the impacts to be reduced is the waste generation. The first step to implement measures to implement a waste management plan at a University is to know the composition, the amount and the distribution of the waste generated in its facilities. As the waste composition and generation depend among other things on the climate, these variables should be analysed over one year. This research work estimates the waste generation and composition of a Spanish University, the Universitat Jaume I, during a school year. To achieve this challenge, all the waste streams generated at the University have been identified and quantified emphasizing on those which are not controlled. Furthermore, several statistical analyses have been carried out to know if the season of the year or the day of the week affect waste generation and composition. All this information will allow the University authorities to propose a set of minimization measures to enhance the current management.